Identification and Analysis of Bacterial Contamination of Ultrasound Transducers and Multiuse Ultrasound Transmission Gel Bottle Tips Before and After the Aseptic Cleansing Technique. (27th April 2020) - Mullins, Kevin; Burnham, Kevin; Henricson, Erik K.; Cohen, Stuart; Fair, James; Ray, Jeremiah W.
Abstract : Objectives: To provide a descriptive analysis for species identification of culture and Gram stain results from ultrasound transducers and multiuse ultrasound transmission gel bottle tips in active clinical use and to compare bacterial cultures from ultrasound transducers before and after aseptic cleansing. Methods: A prospective blinded descriptive analytic study of 18 distinct clinical care sites within a single primary clinical institution was conducted. Before and after a disinfectant towel cleanse, transducers were pressed against tryptic soy agar contact plates. Plates were deidentified and submitted for blind incubation, Gram staining, and species identification with microsequencing. Results were classified as clinically relevant (CR) or non–clinically relevant. In total, 188 samples were analyzed: 80 from ultrasound transducers before and cleansing, 13 from multiuse gel bottle tips before and after cleansing, and 2 precleansing samples from the data collector's pen and badge. Results: Fifty‐nine precleansing samples (73.8%) grew cultures with CR bacteria, and 21 samples (26.3%) did not. Staphylococcus simulans represented 31.0% of all positive culture samples. Thirteen postcleansing samples (16.3%) grew cultures with CR bacteria, equating to a 78.0% reduction of CR bacterial growth (likelihood ratio, 57.10; P < .001). Conclusions: Ultrasound transducers have a notable CR bacterial burden and may serve as potential infective vectors. Aseptic cleansing effectively eliminates most of the bacterial load from ultrasound transducers, but some bacteria persist, presenting a risk of nosocomial infection with ultrasound‐guided interventions. These findings support American Institute of Ultrasound in Medicine 2018 guidelines intended to ensure an appropriate level of transducer preparation based on the examination type while emphasizing rational infection control measures to minimize the risk of potential patient harm.